PENERAPAN KODE ETIK JURNALISTIK PADA PENULISAN BERITA AHOK TERKAIT PEMILUKADA DKI JAKARTA 2017 DALAM SURAT KABAR KOMPAS - MRR Tiyas Maheni; Sari Puspita Dewi; Ade Haryani (Epigram, 2017)
AbstractThis research is aimed at describing the application of Journalistic Code of Ethics on news writing related to Ahok in Governor Election of 2017 published by Kompas. The method used is content analysis as in qualitative approach, then the data analysis technique used is a filling system by making the categories based on the Articles 3, 4 and 8 of Journalistic Code of Ethics to classify the obtained data. Results of the study showed that during July to August 2016 Kompas published 4 (four) news articles and applied almost all of the Articles which are the Article 3 paragraph (b), (c), (d), Article 4 paragraph (a), (b), (c), (d), (e), and Article 8 paragraph (a), (b) on its news articles. Only 1 (one) news article which did not apply the Article 3 paragraph (a) about clarifying information.Key words: Journalistic code of ethics, news articles, governor election